Two decades of oligotrophication: Evidence for a phytoplankton community shift in the coastal lagoon of Thau (Mediterranean Sea, France). (31st August 2020) - Derolez, Valérie; Soudant, Dominique; Malet, Nathalie; Chiantella, Claude; Richard, Marion; Abadie, Eric; Aliaume, Catherine; Bec, Béatrice
Abstract: Mediterranean costal lagoons have been exposed to anthropic eutrophication for decades. Thau lagoon is one of the largest among them and provides many ecosystem services including shellfish farming. Considerable efforts were made between the 1970s and the late 2000s to improve the wastewater treatment systems in the lagoon watershed. A decrease in nutrient inputs to Thau lagoon was subsequently observed, evidence for the start of a recovery process in Thau lagoon, following oligotrophication. This decrease has significant consequences for ecosystem communities, above all primary producers. In our study, we characterised and quantified long-term changes by analysing long monitoring time-series (1998–2016) of phytoplankton biomass, abundance and composition of the taxa, nutrients and climate conditions, using univariate and multivariate statistics. Our results revealed that two decades of mitigation actions in the Thau lagoon watershed have led to a significant progressive reduction in nutrient concentrations and in phytoplankton biomass (−60%), associated with a decrease in diatom abundance (−66%), particularly affecting Skeletonema spp. The changes were associated with a community shift characterised by a shift in phytoplankton taxonomic dominance from Skeletonema-Chaetoceros to Chaetoceros-Pseudo-nitzschia . The median proportion of dinoflagellates relative to diatoms increased, although the total dinoflagellate abundance did not change significantly. We hypothesise that the shift in phytoplankton communities is the result of the mixed effects of the reduction in nutrient inputs and of climatic-related variables. Finally, we present a conceptual scheme of the main drivers of phytoplankton community structure to clarify the ecosystem functioning of a Mediterranean lagoon used for shellfish farming, under oligotrophication and climate change. Highlights: The decrease in water nutrients confirms oligotrophication in the period 1998–2016. The decrease in phytoplankton biomass (−60%) was associated with a decrease in diatom abundance (−66%). A change in phytoplankton community structure was observed with a shift from Skeletonema - Chaetoceros to Chaetoceros - Pseudo-nitzschia dominance . The median proportion of dinoflagellates relative to diatoms increased significantly, although the total dinoflagellate abundance did not change significantly.